Anticoagulant effects of dabigatran on coagulation laboratory parameters in pediatric patients: combined data from five pediatric clinical trials : stroke, systemic or venous thromboembolism - Mitchell, Lesley G.; Röshammar, Daniel; Huang, Fenglei; Albisetti, Manuela; Brandão, Leonardo R.; Bomgaars, Lisa; Chalmers, Elizabeth; Halton, Jacqueline; Luciani, Matteo; Joseph, David; Tartakovsky, Igor; Gropper, Savion; et al. (Thrombosis and haemostasis, 2022)
Background Dabigatran etexilate, a direct oral thrombin inhibitor, is approved to treat venous thromboembolism (VTE) in both adults and children. Objectives This population analysis characterized relationships between dabigatran total plasma concentrations and coagulation laboratory parameters (activated partial thromboplastin time [aPTT]; diluted thrombin time [dTT]; ecarin clotting time [ECT]). Methods Data from three phase 2a and one single-arm and one randomized, comparative phase 2b/3 pediatric studies (measurements: aPTT 2,925 [N = 358]; dTT 2,348 [N = 324]; ECT 2,929 [N = 357]) were compared with adult data (5,740 aPTT, 3,472 dTT, 3,817 ECT measurements; N = 1,978). Population models were fitted using nonlinear mixed-effects modeling. Covariates (e.g., sex, age) were assessed on baseline and drug-effect parameters, using a stepwise covariate model-building procedure. Results Overall, relationships between dabigatran, aPTT, dTT, and ECT were similar in children and adults. For children aged <6 months, a higher proportion of baseline samples were outside or close to the upper aPTT and ECT adult ranges. No age-related differences were detected for dTT. With increasing dabigatran concentration, aPTT rose nonlinearly (half the maximum effect at 368 ng/mL dabigatran) while dTT and ECT increased linearly (0.37 and 0.73% change per ng/mL dabigatran, respectively). Mean baseline aPTT (45 vs. 36 seconds) and ECT (40 vs. 36 seconds) were slightly increased for those aged <6 months versus older children. Conclusion The similar relationships of laboratory parameters observed across pediatric age groups suggests that developmental changes in the hemostatic system may have little effect on response to dabigatran.